A survey of library school faculty in the Philippines - Montes, Angelita L. (1984)
This survey was conducted to draw a profile of library science teachers throughout the country in terms of their personal characteristics, academic background and experience, workload, teaching methods, research output, membership in associations and expressed needs and concerns.